СОВРЕМЕННОЕ СОСТОЯНИЕ ВОДОСНАБЖЕНИЯ НАСЕЛЕНИЯ В УСЛОВИЯХ РЕСПУБЛИКИ КАРАКАЛПАКСТАН - Мираметова, Н.П. (SCIENCE and SOCIETY, 2024)
The article the results of researches of ecological problems of water-supply and adaptation reactions of organism of children are driven to the terms of Priaralye. The modern state is related to considerable the consumption of underwaters both for a water-supply and for irrigation and not always directed in a necessary for a man side. The changes of hydrogeological situation create the special anthropogenic dynamic quality of natural environment and health of population often.